Exploring Anxiety in Learning English During The Emergency Remote Teaching in Islamic Senior High School - Hanafie, Muhammad Ichsan; Santosa, Made Hery; Mahendrayana, Gede (Jurnal Inovasi dan Teknologi Pembelajaran, 2022)
Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat kecemasan siswa dan guru SMA islami serta cara mereka dalam mengurangi kecemasan dalam pembelajaran bahasa Inggris selama pengajaran jarak jauh darurat. Metode penelitian campuran menggunakan kuesioner dan panduan wawancara untuk memperoleh data. Peserta penelitian ini adalah 126 siswa dan empat guru bahasa Inggris di MAN 1 Jembrana. Hasil kuesioner menunjukkan skor rata-rata kecemasan siswa adalah 3,25 yang termasuk dalam kategori kecemasan sedang. Sedangkan hasil skor rata-rata kecemasan pada keempat guru bahasa Inggris yang telah disebar menunjukkan skor 1,8 dan termasuk pada kategori kecemasan rendah. Selanjutnya, hasil panduan wawancara terstruktur menunjukkan bahwa siswa merasakan cemas ringan pada pembelajaran bahasa Inggris selama emergency remote teaching sedangkan guru merasa cenderung tenang dan percaya diri.Abstract: This study focuses on knowing the level of anxiety of Islamic high school students and teachers and how they reduce anxiety in learning English during emergency remote teaching. Mixed methods were used with questionnaires and interview guides to obtain data. The participants of this study were 126 students and four English teachers at MAN 1 Jembrana. The results of the questionnaire showed the mean score of students' anxiety was 3,25 which was included in the category of moderate anxiety. Meanwhile, the mean score of the four English teachers who have been distributed shows a score of 1,8 and is included in the category of low anxiety. Furthermore, the results of the structured guide interviews showed that students felt mild anxiety in learning English during emergency distance teaching, while teachers felt relaxed and confident.